Rancang Bangun Real Time Monitoring & Controlling Infant Incubator Dengan Tilt Stabilizer Untuk Mengurangi Kemiringan Saat Pemindahan Bayi Menggunakan Rasberry PI Berbasis IOT - Syaiful Romadhon; Abdul Multi (Institut Sains dan Teknologi Nasional, 2023)
Abstract The rapid advancement of technology requires innovation to introduce superior features compared to existing technologies, including in the field of healthcare, such as infant incubators. Currently, there is no infant incubator that incorporates an automatic tilt stabilizer, even though the inclination values have been specified and established by the Indonesian National Standard with a recommended 5° inclination during regular usage and a 10° inclination during baby transfers Therefore, The Design and Development of an Infant Incubator with a Tilt Stabilizer for Reducing Tilting During Baby Transfers Using Raspberry Pi-based IoT was undertaken. This research uses an experimental method to achieve the desired performance, following these steps: collecting data and information, controller determination, hardware design, circuit schematics, software design, and user interface website design. Raspberry Pi was chosen as the controller due to its sufficient input and output (GPIO) pins to read sensors and operate actuators. The tilt stabilizer was created usings NEMA17 stepper motor and self-designed flexible screw nut to ensure precise tilt adjustment. During testing, the system demonstrated reliable performance. This was verified by analyzing the test data and sensor readings displayed on the HDMI-connected screen, concurrently with the data presentation on the website. The temperature graph inside the incubator consistently maintained a value of 37°C with a deviation of 2°C using the PID control methode. The incubator's tilt, when transferred to an inclined surface of 20°, remained stable at 10° when the tilt stabilizer was activated. Keywords: Infant incubator, Tilt stabilizer, Raspberry Pi, IoT, Sensor.